Inactivation of Viable Ascaris Eggs by Reagents during Enumeration - Nelson, Kara L. (American Society for Microbiology, 2001)
Various reagents commonly used to enumerate viable helminth eggs from wastewater and sludge were evaluated for their potential to inactivate Ascaris eggs under typical laboratory conditions. Two methods were used to enumerate indigenous Ascaris eggs from sludge samples. All steps in the methods were the same except that in method I a phase extraction step with acid-alcohol (35% ethanol in 0.1 N H(2)SO(4)) and diethyl ether was used whereas in method II the extraction step was avoided by pouring the sample through a 38-μm-mesh stainless steel sieve that retained the eggs. The concentration of eggs and their viability were lower in the samples processed by method I than in the samples processed by method II by an average of 48 and 70%, respectively. A second set of experiments was performed using pure solutions of Ascaris suum eggs to elucidate the effect of the individual reagents and relevant combination of reagents on the eggs. The percentages of viable eggs in samples treated with acid-alcohol alone and in combination with diethyl ether or ethyl acetate were 52, 27, and 4%, respectively, whereas in the rest of the samples the viability was about 80%. Neither the acid nor the diethyl ether alone caused any decrease in egg viability. Thus, the observed inactivation was attributed primarily to the 35% ethanol content of the acid-alcohol solution. Inactivation of the eggs was prevented by limiting the direct exposure to the extraction reagents to 30 min and diluting the residual concentration of acid-alcohol in the sample by a factor of 100 before incubation. Also, the viability of the eggs was maintained if the acid-alcohol solution was replaced with an acetoacetic buffer. None of the reagents used for the flotation step of the sample cleaning procedure (ZnSO(4), MgSO(4), and NaCl) or during incubation (0.1 N H(2)SO(4) and 0.5% formalin) inactivated the Ascaris eggs under the conditions studied.